Where are nutritious diets most expensive? Evidence from 195 foods in 164 countries - Alemu, Robel; Block, Steven A.; Headey, Derek D.; Bai, Yan; Masters, William A. (2019)
Food prices vary widely around the world, depending on the local cost of retail services and supply chains as well as farm supply and the border prices of tradable commodities. This study measures the cost of the most affordable nutritionally adequate diet in each country, relative to the cost of dietary energy and other benchmarks such as national income and poverty lines, so as to identify development paths associated with lower cost access to the nutrients needed for a healthy and active life. We use prices for 195 standardized food and beverage items across 164 countries in 2011 collected by the World Bank's International Comparison Project (ICP), matched with data on these items' composition in terms of 21 essential nutrients and each nutrient's lower and upper limits for a healthy adult woman. Using a subsample of 134 countries for which economic structure data are available, we find that the cost of nutrient adequacy is highest in poorer and middle-income countries, and is highe